An assembled bacterial community associated with Artemisia annua L. causes plant protection against a pathogenic fungus - Wang, Yu; Yang, Zhan-nan; Luo, Shi-qiong (Frontiers in Microbiology, 2023)
The microorganisms associated with a plant influence its growth and fitness. These microorganisms accumulate on the aerial and root surfaces of plants, as well as within the plants, as endophytes, although how the interaction between microorganisms protects the plant from pathogens is still little understood. In the current study, the impact of assembled the bacterial communities against the pathogenic fungus to promote Artemisia annua L. growths was investigated. We established a model of bacterium-fungus-plant system. Eight bacterial strains and a fungal pathogen Globisporangium ultimum (Glo) were isolated and from wild A. annua leaves and roots, respectively. We assembled the six-bacteria community (C6: Rhizobium pusense, Paracoccus sp., Flavobacterium sp., Brevundimonas sp., Stenotrophomonas sp., and Bacillus sp.) with inhibition, and eight-bacteria community (C8) composing of C6 plus another two bacteria (Brevibacillus nitrificans and Cupriavidus sp.) without inhibition against Glo in individually dual culture assays.Inoculation of seedlings with C8 significantly reduced impact of Glo. The growth and disease suppression of A. annua seedlings inoculated with C8+Glo were significantly better than those of seedlings inoculated with only Glo. C8 had more inhibitory effects on Glo, and also enhanced the contents of four metabolites in seedling roots compared to Glo treatment only. Additionally, the inhibitory effects of root extracts from A. annua seedlings showed that Glo was most sensitive, the degree of eight bacteria sensitivity were various with different concentrations. Our findings suggested that the noninhibitory bacteria played a vital role in the bacterial community composition and that some bacterial taxa were associated with disease suppression. The construction of a defined assembled bacterial community could be used as a biological fungicide, promoting biological disease control of plants.